2016
DOI: 10.46743/2160-3715/2016.2300
|View full text |Cite
|
Sign up to set email alerts
|

Using Interpretative Phenomenological Analysis from a Realist Perspective

Abstract: The article presents how a study that investigated the acquisition of second language academic literacy skills practised the qualitative methodology, interpretative phenomenological analysis (IPA), from a realist perspective. We share the rationale behind the methodological decisions made in the study, which is followed by a detailed description of the methodological practice. In addition, the evaluation of the study against the realist criteria is reported, and some implications of using IPA based on realism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
0
23
0
2
Order By: Relevance
“…The IPA literature does not explicitly recommend any particular method of data analysis (Pringle et al, 2011). However, a thorough critical exploration of a range of studies (Fade, 2004;Smith and Osborn, 2008;Palmer et al, 2010;Pietkiewicz and Smith, 2012;Jeong and Othman, 2016) reveals that most authors follow approaches similar to that suggested by Smith et al, (2009, pp. 82-101).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPA literature does not explicitly recommend any particular method of data analysis (Pringle et al, 2011). However, a thorough critical exploration of a range of studies (Fade, 2004;Smith and Osborn, 2008;Palmer et al, 2010;Pietkiewicz and Smith, 2012;Jeong and Othman, 2016) reveals that most authors follow approaches similar to that suggested by Smith et al, (2009, pp. 82-101).…”
Section: Discussionmentioning
confidence: 99%
“…IPA analysis is not complete until the researcher writes up the findings (Smith et al, 2009); indeed, the writing up process itself may help the analyst to make further sense of the data, themes and sub-themes. As part of the process of communicating individual stories, themes may be reduced or combined (see Smith et al, 2009;Jeong and Othman, 2016). The writing up process can also be seen as an interpretative engagement with the participants experience or a conversation with participants and the researcher.…”
Section: Writing Upmentioning
confidence: 99%
“…We transcribed word by word from the interviews that were recorded and coded manually. After data encoding, we conducted data analysis using Interpretative Phenomenological Analysis (IPA) (Jeong & Othman, 2016). In the first step, we re-read the transcript results until we found the information that had not been recorded in the initial reading.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that to study experience, a phenomenological approach is the most widely recommended method (Neubauer, Witkop, & Varpio, 2019). The use of IPA in English language education has also been conducted in Malaysian context, such as (Jeong & Juliana Othman, 2016), in which the researchers studied the issue of second language acquisition. This indicates that the phenomenological framework is an appropriate modus operandi to study the intertwining issues between English language education and management.…”
Section: Methodsmentioning
confidence: 99%